Long-term Outcomes of Treat and Extend Regimen of Anti-vascular Endothelial Growth Factor in Neovascular Age-related Macular Degeneration - Andy Lee; Pooja G Garg; Alice T Lyon; Rukhsana Mirza; Manjot K Gill (Journal of Ophthalmic & Vision Research, 2020)
Purpose: This study describes the long-term visual and anatomic outcomes of anti-vascular endothelial growth factor (VEGF) treatment using a treat and extend dosing regimen. Methods: This cross-sectional cohort study consisted of 224 treatment-naïve eyes with neovascular age-related macular degeneration (NV-AMD) from 202 patients that were treated with anti-VEGF agents bevacizumab, ranibizumab, and aflibercept using a treat and extend (TAE) regimen by four physician investigators in a large urban referral center from 2008 to 2015. Subjects were evaluated for visual acuity, injection frequency, and optical coherence tomography (OCT). Results: Over a seven-year follow-up period (mean 3.4 years), an average 20.2